An Exceptional Case of Liver-Restricted High-Grade B-Cell Lymphoma in a Patient with Clinical History of HBV and HCV Coinfections - Connor R. Zuraski; Vinit Patil; Katherine E. Schwetye (Hindawi Limited, 2019)
Primary hepatic lymphomas (PHLs) are exceedingly rare. Many reported cases are associated with various viral serologies, and some viruses may be implicated in lymphomagenesis through emerging, though as-of-yet uncertain, mechanisms. A review of the literature reveals previously reported cases of PHL, some of which support the potential roles of the hepatitis B and C viruses (HBV and HCV) in the development of PHL. We describe an exceptional case of primary hepatic high-grade B-cell lymphoma, discovered at autopsy, in a patient whose clinical history is significant for coinfection with both HBV and HCV. Additionally, attempts at cytogenetic testing of formalin-fixed, paraffin-embedded (FFPE) autopsy tissues, which we performed approximately ten years after the original autopsy, led us to question the utility of older tissue blocks in molecular and some immunohistochemical assays.